Case Report: Balancing immune responses – multiple sclerosis disease exacerbation under BRAF/MEK treatment for malignant melanoma - Pape, Katrin; Protopapa, Maria; Schraad, Muriel; Steffen, Falk; Zipp, Frauke; Bittner, Stefan (Frontiers in Oncology, 2023)
Background: Combination treatment with BRAF/MEK inhibitors favorably impact progression-free survival in malignant melanoma. However, it may cause paradoxical activation of the MAPK/ERK pathway in immune cells without BRAF mutation, which may lead to over activation of the immune system, especially in patients with pre-existing autoimmune conditions. In this case report, treatment of malignant melanoma with BRAF/MEK inhibitors was associated with radiological disease exacerbation of pre-existing multiple sclerosis (MS). Case presentation: A 47-year-old patient with pre-existing MS was diagnosed with malignant melanoma in June 2020. Anti-tumor treatment was initiated with a combination therapy of BRAF inhibitor dabrafenib and MEK inhibitor trametinib. In February 2022, the patient presented at our neurological clinic after routine MRI revealed exacerbation of radiological MS disease activity with ten new and gadolinium-enhancing lesions, and concomitant high levels of neurofilament light chain (NfL) in serum, a marker for axonal damage. In-depth analysis of immune cells in both peripheral blood and cerebrospinal fluid was performed by multi-color flow cytometry. After treatment with the B-cell-depleting antibody ocrelizumab, MS disease stability was obtained and anti-tumor medication could be continued. Conclusions: Immunomodulatory treatment in cancer patients is highly effective from an oncological point of view, but may be associated with autoimmune side effects. This is of special importance in patients with pre-existing autoimmune diseases, as reflected by our case of MS disease reactivation under treatment with BRAF/MEK inhibitors. In our case, sequential modulation of immune cell subsets by B cell depletion, associated with marked shifts in B and T cell subsets, allowed for stabilization of disease and continuation of anti-tumor treatment.